Plasma signature of apoptotic microvesicles is associated with endothelial dysfunction and plaque rupture in acute coronary syndromes. (January 2020) - Zacharia, Effimia; Antonopoulos, Alexios S.; Oikonomou, Evangelos; Papageorgiou, Nikolaos; Pallantza, Zoi; Miliou, Antigoni; Mystakidi, Vasiliki Chara; Simantiris, Spyridon; Kriebardis, Anastasios; Orologas, Nikolaos; Valasiadi, Eftychia; Papaioannou, Spyridon; et al.
Abstract: Objective: Circulating microvesicles (MV) are surrogate biomarkers of atherosclerosis. However, their role in acute coronary syndromes (ACS) has not been fully elucidated yet. We sought to examine the association of circulating apoptotic MVs with ACS pathophysiology. Approach and results: One hundred and fifty-three patients ( n = 153) were included in the study; 49 patients with ST-elevation myocardial infarction (STEMI), 35 with non-STEMI (NSTEMI), 38 with unstable angina, 15 with stable coronary artery disease and 16 control individuals. Flow cytometry analysis was used to quantify circulating apoptotic/non-apoptotic (phospatidyloserine + /phospatidyloserine − ) endothelial cell (EMV), red blood cell (RMV) and platelet (PMV) derived MV. Flow-mediated dilatation (FMD) of the brachial artery was assessed by ultrasound to estimate endothelial function. The inflammatory profile was assessed by serum C-reactive protein (hsCRP) levels. Apoptotic only (but not non-apoptotic) MV were increased in patients with ACS (EMV, P = 2.32 × 10 −9 ; RMV, P = .0019; PMV, P = .01). Hierarchical clustering of the total population of ACS patients ( n = 122) by circulating levels of phospatidyloserine + EMV, RMV and PMV identified two discreet clusters of patients without any differences in traditional risk factors, but significant differences in brachial FMD (5.2% (2.5) vs. 4.1% (2.3), P < .05) that remained significant after adjustment for co-variates. The prevalence of STEMI, a surrogate for plaque rupture and vessel thrombotic occlusion, was significantly higher in the patient cluster with impaired endothelial function (60% vs 32%, P = .016, adjusted odds ratio for STEMI, 3.041, 95%CI, 1.160 to 7.968, p = .024). Conclusion: Our findings indicate that the circulating levels of apoptotic MV are increased in ACS patients and their plasma profiles associate with endothelial dysfunction and thrombotic complications in ACS patients. Highlights: Plasma levels of apoptotic cell-derived microvesicles are significantly increased in patients with acute coronary syndromes A distinct signature of plasma apoptotic microvesicles is related to worse endothelial function in patients with ACS. This distinct signature of microvesicles is also related to higher OR for STEMI in the absence of differences in risk profile. These findings provide evidence on the role of plasma microvesicles in the pathophysiology of ACS and plaque rupture.